On the algebraic structure of Klimov-Shamir T-function - LUO Yong-long; QI Wen-feng (Tongxin xuebao)
The algebraic structure of Klimov-Shamir T-function was studied,and some algebraic equations over the bina-ries of sequences generated by this T-function were presented.According to these equations,how to choose C which could make the algebraic structure of this T-function more complicated was preliminarily discussed.